A Comparative Study on Pure and Mg Doped ZnO Nano Structured Thin Films - Vijayaprasath1, G.; Ravi1, G.; Manik, M.R.; Arivananhan2, M.; Navaneethan2, M.; Hayakawa2, Y. (Asian Journal of Chemistry, 2013)
Pure and Mg doped zinc oxide thin films were prepared on glass substrates by chemical bath deposition method. These films were characterized for their structural, morphological, optical and functional properties by means of powder X-ray diffraction, scanning electron microscopy, UV-visible spectroscopy and Raman analysis. Powder XRD results showed that ZnO nano crystallites have hexagonal structural phase. SEM micrographs revealed homogeneous flower shaped structures for pure ZnO thin films and flower petals were bound to the spherical shape for the case of Mg doped ZnO. Optical and functional properties of the films were studied from UV-visible and Raman analyses respectively.